INDONESIAN BANKS RISK-TAKING: THE EFFECT OF RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS AND CAPITAL (RGEC) - Hamdi; Lasma Melinda Siahaan; Muhammad Farhan Syarkawi; Utami Handayani (Journal of Social and Economics Research, 2026)
This study examines the effect of RGEC framework, comprises four key components: Risk Profile, Good Corporate Governance, Earnings, and Capital, on the risk-taking behavior of banks in Indonesia. Banks’ risk-taking behavior is proxied by the Z-Score, which reflects bank stability and insolvency risk. Within the RGEC framework, risk profile is proxied by Non-Performing Loans (NPLs), Good Corporate Governance is proxied by Institutional Ownership (INST), earnings is proxied by Operational Inefficiency (BOPO), and capital is proxied by Capital Adequacy Ratio (CAR). This study employs a quantitative approach using a dynamic panel data regression model estimated with the two-step System Generalized Method of Moments (GMM). The sample consists of 33 banks listed on the Indonesia Stock Exchange (IDX) over the period 2017–2022, using secondary data obtained from banks’ annual financial statements. The empirical results indicate that Non-Performing Loans (NPLs), Institutional Ownership, and Operational Inefficiency (BOPO) have a negative and significant effect on the Z-Score, suggesting that higher credit risk, stronger institutional ownership, and lower operational efficiency increase banks’ risk-taking behavior. In contrast, the Capital Adequacy Ratio (CAR) has a positive but insignificant effect on the Z-Score, indicating that higher capital adequacy tends to reduce banks’ risk-taking behavior, although the effect is not statistically significant. Overall, the findings highlight the importance of RGEC components in explaining variations in risk-taking behavior among Indonesian banks and provide relevant insights for banking regulators and bank management in strengthening prudential supervision and risk governance.